Assessment of structural integrity of subsea wellhead system: analytical and numerical study - A.R. Maligno; R. Citarella; V.V. Silberschmidt; C. Soutis (Fracture and Structural Integrity)
Subsea wellhead systems exposed to severe fatigue loading are becoming increasingly a significant problem in offshore drilling operations due to their applications in wells with higher levels of pressure and temperature, situated at larger depths and in harsher environments. This has led to a substantial increase in the weight and size of offshore equipment, which, in combination with different loading conditions related to the environmental factors acting on the vessel and riser, has greatly increased the loads acting on subsea well systems. In particular, severe fatigue loading acting on the subsea wellhead system was detected. For this reason, a combined analytical and numerical study investigating the critical effect of crack depth on the overall structural integrity of subsea wellhead systems under cyclic loading was carried out. The study is based on a Linear Elastic Fracture Mechanics (LEFM) approach.